The Turmoil of Europe’s Economy, Food and Energy Stability: Will It Ends Western Sanctions on Russia? - Yassar Nandana; Arthur Josias Simon Runturambi; Eko Daryanto (Ridwan Institute, 2023)
Ukrainian and Russian War had a significant impact on the European economy, food, and energy. As one of the strategy to stop the war, the Western had imposed several sanctions on Russia that raised critical questions on whether or not this sanction is an appropriate and effective measure that should be pursued. Reflecting on history, economic weapons through economic sanctions are often ineffective against big countries that do have resilience. Not only that, the view that sanctions will suppress aggressive actions when material interests are disturbed is not always an appropriate case considering that countries and their leaders, especially autocratic ones, have other priorities. Through this articles, we’re going to discuss how the turmoil of Europe’s economy, food and energy stability may affect Western decisions to end their sanction to Russia. We concludes that the West, especially Europe, has no other way but to negotiate with Russia to carry out a ceasefire and negotiations regarding gas & oil supplies and in turns will end Western sanction to Russia gradually.